. Prognostic value of serum IL-2, IFN-γ, TNF-α, IL-6, and IL-8, IL-10 in elderly Patients underwent Thoracotomy : Prognostic value of serum IL-2, IFN-γ, TNF-α, IL-6, and IL-8, IL-10 - Chen, Jia; Meng, Lifeng (Journal of Medical Biochemistry, 2025)
Objective: To investigate the effect of different fluid therapy on TH1 and TH2 cytokines ( IL-2, IFN-γ, TNF-α, IL-6, and IL-8 , IL-10 ) during perioperative period of thoracotomy in elderly patients. Methods:A total of 60 elderly patients who underwent thoracotomy from January 2022 to April 2024 were divided into the control group (CG) and the observation group (OG), with 30 cases in each group. The CG received routine fluid management, while the OG received goal-directed fluid management. The postoperative recovery status, fluid intake and output, hemodynamic indexes, TH1 and TH2 cytokine levels were compared between both groups. Results: The postoperative extubation time, drainage time, ICU stayand hospitalization time in the OG were reduced than those in the CG (P<0.05). The urine volume, crystalloid volume, colloid volume and total volume of fluid in the OG werereduced than those in the CG (P<0.05). At 1 h after surgery (T2), the HR and MAP levels of the two groups were reduced than those before surgery (T1) (P<0.05); at the end of surgery (T3), the HR and MAP of the CG were raised than those at T1 (P<0.05); at T2, the HR and MAP levels in the OG were raised than those in the CG (P<0.05); at T3, the HR and MAP levels in the OG were reduced than those in the CG (P<0.05). 1 day after operation, the levels ofIL-2, IFN-γ, TNF-α, IL-6, and IL-8 were raised than those before surgery, (P<0.05), and the levels of IL-10 wasreduced than those before treatment (P<0.05). Conclusion: Perioperative goal-directed fluid therapy for elderly patients with thoracotomy is beneficial to maintain perioperative hemodynamic stability, improve serum levels of TH1 and TH2 cytokines, reduce the body’s inflammatory response, and facilitate early postoperative recovery.